Efektivitas Sistem Informasi Penatih (SIPENA) pada Kelurahan Penatih Kecamatan Denpasar Timur dalam Mempercepat Pelayanan Administratif - Maharani, Ni Nyoman Sintia; Yasintha, Putu Nomy; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2023)
Penatih Village, East Denpasar District implemented an administrative service through the Penatih Information System (SIPENA). The concept is a development of the current Management Information (SIM) which demands a transformation of traditional government bureaucracy towards E-Government which aims to overcome problems in service delivery, such as the convoluted manual work system of village employees, the process of issuing the application letter is to long, and errors in collecting population data. This research measured by the effectivenes of service accoding to Richard M. Steers. Using the descriptive qualitative method, with data collection techniques in the from of observation, interviews, and documentation. The results of research shows that the effectiveness of the SIPENA in accelerating administrative service has not been maximized. Based on three indicatorrs used to see the efectiveness of administrative services that still encounter some obstacles in each of indicator. Keywords: Effectiveness, SIPENA, E-Government, Management Information System